10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Neurocognitive demands during sport-specific tasks may influence movement patterns associated with anterior cruciate ligament (ACL) injury risk, but the effect of baseline cognitive-motor function remains unclear. This study investigated whether baseline cognitive-motor performance is associated with ACL injury-related biomechanics during landing tasks with increasing cognitive demands. Hypotheses (1) People with lower baseline cognitive scores would exhibit riskier movement patterns, and (2) cognitive load would negatively influence ACL-related biomechanics. Study design Cross-sectional observational laboratory study. Level of evidence Level 4. Methods A total of 50 healthy athletes completed baseline cognitive-motor testing for reaction time (872 ± 90 ms), processing speed (83 ± 14%), divided attention (58 ± 14%), and peripheral vision (69 ± 12%), followed by a jump-land-jump task under anticipated (ANT), unanticipated (UNA), and cognitively-challenging (COG) conditions involving peripheral vision. Peak lower-limb kinematics and kinetics were recorded, and mixed-effects models were used to evaluate the effects of cognitive-motor load and baseline function on biomechanical outcomes. Results Baseline cognitive-motor performance showed limited associations with landing biomechanics during valid trials, with isolated relationships observed for hip flexion and adduction angles (P = 0.05 and P = 0.04, respectively). Lower peripheral vision accuracy (P < 0.001) and higher processing speed (P < 0.001) were significantly associated with a greater incidence of errors during nonanticipated conditions (error rates: ANT 0%, UNA 2.8%, COG 35.5%). Increasing cognitive load consistently induced biomechanical changes associated with greater ACL loading markers (P = 0.02 to <0.004), including increased knee abduction angles and moments and reduced joint flexion, with significant differences between ANT and both UNA and COG conditions. Conclusion While baseline cognitive-motor function may have a limited influence on correctly executed movement biomechanics in healthy athletes, specific cognitive domains are related to task execution errors under cognitively demanding conditions, notably including higher processing speed. Increased cognitive-motor demands involving unanticipation and peripheral vision systematically altered landing mechanics toward potentially higher-risk patterns. Clinical relevance Assessing baseline cognitive-motor function and sport-specific demands may help inform ACL injury risk screening strategies. Failed trials represent an additional dimension to be considered for investigating the influence of cognitive factors on ACL injury biomechanics.